Mathematical Critical Thinking Ability in Terms of Students Learning Motivation in Probing Prompting Learning (Unnes Journal of Mathematics Education, 2022)
This research aimed (1) to analyze the effectiveness of Probing Prompting learning on students' mathematical critical thinking skills and (2) to describe mathematical critical thinking skills in terms of students' learning motivation in learning with the Probing Prompting model. This research method was a combination research method (mixed method) with the type of Explanatory Sequential Design. The results showed that: (1) the mathematical critical thinking ability of the Probing Prompting class achieved classical completeness; (2) the proportion of mathematical critical thinking skills in the Probing Prompting class is more than the proportion of mathematical critical thinking skills in the Problem Based Learning class; (3) the average mathematical critical thinking ability of the Probing Prompting class is more than the average mathematical critical thinking ability of the Problem Based Learning class. Subjects with high learning motivation are able to meet all indicators of mathematical critical thinking skills, namely indicators of clarification, assessment, inference, and strategies. Subjects with moderate learning motivation tend to be able to fulfill the clarification indicators; less able to meet the assessment indicators; tend to be able to meet the inference indicators; and able to meet the indicators of strategies. Subjects with low learning motivation tend to be able to fulfill the indicators of clarification, less able to meet the assessment indicators, less able to meet the inference indicators, and tend to be able to meet the indicators of strategies.